Circular RNA hsa_circ_0072309 inhibits proliferation and invasion of breast cancer cells via targeting miR-492 - Yan, Lin (Cancer Manag Res, 2019)
BACKGROUND: Although the number of circular RNAs (circRNAs) that has been identified in multiple cancer tissues continues to increase, the relationship between circRNA expression and carcinogenesis remains unknown. The role of hsa_circ_0072309 in breast cancer has remained undefined until now. In this study, we aimed to investigate the role of hsa_circ_0072309 in breast cancer progression. METHODS: hsa_circ_0072309 expression in breast cancer tissues was analyzed using qRT-PCR. A series of functional experiments were carried out to investigate hsa_circ_0072309 function in breast cancer development and its underlying molecular mechanisms. RESULTS: hsa_circ_0072309 expression in breast cancer tissues was upregulated relative to that in adjacent normal tissues. hsa_circ_0072309 could serve as a prognostic biomarker of breast cancer. hsa_circ_0072309 overexpression dramatically inhibited the proliferation, migration, and invasion of breast cancer cells in vitro. In vivo assays revealed that the ectopic expression of hsa_circ_0072309 repressed breast cancer growth. The results of our mechanistic studies indicated that hsa_circ_0072309 could act as the sponge of miR-492, which exhibited increased expression in breast cancer tissues. Hsa_circ_0072309 suppressed breast cancer cell proliferation, migration, and invasion by inhibiting miR-492. CONCLUSION: Our findings revealed for the first time that the hsa_circ_0072309-miR-492 axis plays an essential role in breast cancer progression.